Safety and efficacy of transarterial embolization of hepatocellular adenomas. Issue 10 (17th July 2019) - van Rosmalen, B. V.; Klompenhouwer, A. J.; de Graeff, J. Jaap; Haring, M. P. D.; de Meijer, V. E.; Rifai, L.; Dokmak, S.; Rawashdeh, A.; Abu Hilal, M.; de Jong, M. C.; Dejong, C. H. C.; Doukas, M.; et al.
Abstract : Background: Hepatocellular adenoma (HCA) larger than 5 cm in diameter has an increased risk of haemorrhage and malignant transformation, and is considered an indication for resection. As an alternative to resection, transarterial embolization (TAE) may play a role in prevention of complications of HCA, but its safety and efficacy are largely unknown. The aim of this study was to assess outcomes and postembolization effects of selective TAE in the management of HCA. Methods: This retrospective, multicentre cohort study included patients aged at least 18 years, diagnosed with HCA and treated with TAE. Patient characteristics, 30‐day complications, tumour size before and after TAE, symptoms before and after TAE, and need for secondary interventions were analysed. Results: Overall, 59 patients with a median age of 33.5 years were included from six centres; 57 of the 59 patients were women. Median tumour size at time of TAE was 76 mm. Six of 59 patients (10 per cent) had a major complication (cyst formation or sepsis), which could be resolved with minimal therapy, but prolonged hospital stay. Thirty‐four patients (58 per cent) were symptomatic at presentation. There were no significant differences in symptoms before TAE and symptoms evaluated in the short term (within 3 months) after TAE ( P = 0·134). First follow‐up imaging was performed a median of 5·5 months after TAE and showed a reduction in size to a median of 48 mm ( P < 0·001). Conclusion: TAE is safe, can lead to adequate size reduction of HCA and, offers an alternative to resection in selected patients. Abstract : Transarterial embolization (TAE) is relatively safe and can lead to adequate size reduction of hepatocellular adenoma. This minimally invasive intervention offers an interesting alternative to resection. Alternative treatment for large adenomas Abstract : Antecedentes: El adenoma hepatocelular ( hepatocellular adenoma, HCA) > 5 cm de diámetro tiene un riesgo mayor de hemorragia y transformación maligna, y se considera una indicación de resección. Como alternativa a la resección, la embolización transarterial ( transarterial embolization, TAE) puede desempeñar un papel en la prevención de complicaciones del HCA, pero su seguridad y eficacia son en gran parte desconocidas. El objetivo de este estudio fue evaluar los resultados y los efectos de la embolización de la TAE selectiva en el tratamiento del HCA. Métodos: Se realizó un estudio de cohortes retrospectivo y multicéntrico que incluyó pacientes de edad ≥ 18 años, diagnosticados de HCA y tratados con TAE. Se analizaron las características de los pacientes, las complicaciones a los 30 días, el tamaño del tumor antes y después de la TAE, los síntomas antes y después de la TAE y la necesidad de intervenciones secundarias. Resultados: En total, 59 pacientes con una mediana de edad de 33, 5 años se incluyeron en seis centros; 57 de 59 pacientes eran mujeres. La mediana del tamaño del tumor en el momento de la TAE fue de 76 mm. Seis de 59 (10%) pacientes tuvieron una complicación mayor (es decir, formación de quistes o sepsis), que pudo resolverse con una terapia mínima, pero ello prolongó la estancia hospitalaria. Treinta y cuatro de 59 (58%) pacientes presentaban síntomas en el momento del diagnóstico. No hubo diferencias significativas en los síntomas antes de la TAE y los síntomas evaluados a corto plazo (< 3 meses) después de la TAE ( P > 0, 050). La primera prueba de imagen de seguimiento se realizó tras una mediana de 5, 5 meses después de la TAE y mostró una reducción en el tamaño del adenoma con una mediana de 48 mm ( P < 0, 001). Conclusión: La TAE es un procedimiento seguro y puede llevar a una reducción adecuada del tamaño del HCA. Esta intervención mínimamente invasiva ofrece una alternativa a la resección.